Reactions to Gudair® vaccination identified in sheep used for biomedical research. Issue 3 (13th February 2019) - Musk, GC; Kershaw, H; Tano, K; Niklasson, A; von Unge, M; Dilley, RJ
Abstract : Case report: We report Gudair® vaccination (against ovine Johne's disease, Mycobacterium avium subsp. paratuberculosis ) site reactions in sheep used as a surgical model in biomedical research and discuss the actual and potential impact these lesions may have on surgical procedures, particularly in otology. Nine female Merino‐cross sheep ( Ovis aries ) were enrolled in a project designed to investigate the healing capabilities of the malleus bone in the middle ear. The sheep were 12–18 months of age. Eight sheep had lesions near the base of the right ear that were discovered when surgery was performed. The size of the lesions varied and all lesions had a thick capsule containing various amount of caseous material. Two lesions had a draining tract where purulent material was apparent at the lowest point. The prescapular lymph nodes were not palpable in any of the sheep. Aerobic growth of various organisms was reported from four sheep lesions when the purulent material was transferred to a broth media. Histopathological examination revealed intralesional Mycobacteria and focal caseous necrosis or granulomatous dermatitis and cellulitis in seven of the eight lesions. Mild necrotising to granulomatous dermatitis and cellulitis was described in the lesion where organisms were not found. Conclusions: The lesions were confirmed at the end of the study to be associated with the vaccination and did not cause any known adverse effects on the research. However, it is important to acknowledge the risk of contamination these lesions could have on a sterile surgical site.